(untitled) (Revista Brasileira Multidisciplinar, 2022)
Melampodium divaricatum is an herbaceous species, naturally occurring in the Northeast regions of Brazil and is known for its medicinal value and the action against oral pathogens. The objective of this study was to verify the synergistic effect and activity against biofilm formation of the EO from M. divaricatum against bacteria associated with dental caries. The checkerboard assays was used to investigate the in vitro antimicrobial efficacy of the combination of Chlorhexidine dichlorohydrate with M. divaricatum EO. The microtitration plate assay was used for determination the Minimum Inhibitory Concentration of Biofilm (MICB50) of essential oil against the bacteria. The synergistic effect and activity against biofilm formation of the essential oil (EO) from M. divaricatum against bacteria associated with dental caries were observed. The combination effects of EO with chlorhexidine were additive to L. casei, antagonic to S. mutans and indifferent to S. sobrinuns and S. mitis. The antibiofilm activity revealed significant results MICB50 values (200 at 400 µg/mL). This report suggests that the EO is a promising natural product to develop novel therapeutic strategies to fight against cariogenic bacteria.